The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1021/acs.jpcc.5b08100
|View full text |Cite
|
Sign up to set email alerts
|

Helical and Nonhelical Structures of Vinylene- and Azomethine-Linked Heterocyclic Oligomers: A Computational Study of Conformation-Dependent Optoelectronic Properties

Abstract: A systematic computational investigation has been carried out at the density functional level of theory to characterize various conformational isomers of furan, pyrrole, and thiophene based oligomers and consequently study their stabilities and electronic properties, especially in the cases of long oligomers. In these oligomers, adjacent heterocyclic rings are connected by either vinylene or azomethine linkages. B3LYP and B3LYP-D3 functionals are used to observe the effect of dispersion energy. Our results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 78 publications
(164 reference statements)
0
10
0
Order By: Relevance
“…In all conformations, they exhibited excellent pelectron delocalization and dense valence and conduction bands. 21 Moreover, it was demonstrated that doping with both electron donor or acceptor species reduced the band gaps and pushed behaviour of the systems towards those typical for metals. 21 Oligothiophenes, oligofurans and oligopyrroles with vinylene or azomethine ring linkers have been recently studied at the B3LYP/6-31G** level combined with and without Grimme's D3 correction.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…In all conformations, they exhibited excellent pelectron delocalization and dense valence and conduction bands. 21 Moreover, it was demonstrated that doping with both electron donor or acceptor species reduced the band gaps and pushed behaviour of the systems towards those typical for metals. 21 Oligothiophenes, oligofurans and oligopyrroles with vinylene or azomethine ring linkers have been recently studied at the B3LYP/6-31G** level combined with and without Grimme's D3 correction.…”
mentioning
confidence: 99%
“…21 Moreover, it was demonstrated that doping with both electron donor or acceptor species reduced the band gaps and pushed behaviour of the systems towards those typical for metals. 21 Oligothiophenes, oligofurans and oligopyrroles with vinylene or azomethine ring linkers have been recently studied at the B3LYP/6-31G** level combined with and without Grimme's D3 correction. 22 Strikingly, the relative stability of the conformers and difference in electronic transitions depended on the linker, but for the azomethine linker also on the heterocycle unit.…”
mentioning
confidence: 99%
See 3 more Smart Citations